The Influence of Intellectual Intelligence, Eional Intelligence and Role Stress on Auditors' Performance Using Spiritual Intelligence and Religiousity as A Moderation of Research in The Riau Province Indonesia Inspectorate - Badewin; Amri Amir; Sri Rahayu; Rike Setiawati (Indonesian Journal of Economic & Management Sciences, 2023)
The research aims to develop a conceptual model of local government auditor performance with intellectual, emotional intelligence, role stress on auditor performance with spiritual intelligence and religiosity as moderation (empirical study at the Riau Province inspectorate). Sample of 123 Inspectorate auditor respondents in Riau Province, Indonesia. SEMwarpPLS software. The results of research on intellectual intelligence, emotional intelligence and role pressure have a positive effect on auditor performance. Meanwhile, the spiritual intelligence moderating variable cannot strengthen intellectual and emotional intelligence on auditor performance and the spiritual intelligence moderating variable can weaken the role of stress on auditor performance. Then religiosity as a moderating variable can influence emotional intelligence and stress can weaken auditor performance. On the other hand, religiosity as moderation cannot strengthen the influence of intellectual intelligence on auditor performance